Municipal solid waste incineration : requirements for a successful project - Rand, T., 1959-; Marxen, U., 1967-; Haukohl, J., 1944-; World Bank. (Washington, D.C. : World Bank, 2000)
To assist local officials with developing cost effective strategies for dealing with solid waste management, the World Bank launched a program to provide high level advice on approaches that support themselves financially and are socially and environmentally responsible. This Technical Paper provides the foundation for such a detailed evaluation of solid waste incineration systems. This volume will be of interest to municipal managers and others concerned with solid waste and incineration projects.
Includes bibliographical references.
oif 16/09/15
Loan
Keywords: Incineration